Efficacy of Topical 10% Isoniazid Cream Versus Triple Combination Cream (Kligman's Formula) in the Treatment of Mixed Melasma - Jabeen, Saadia; Saleem, Summaya; Falak, Asfa; Tanveer, Muhammad; Irshad, Laila; Abid, Rabia (Biological and Clinical Sciences Research Journal, 2025)
Melasma is an acquired pigmentary skin disorder characterized by symmetrical brown patches, most commonly on the face. The standard treatment involves topical triple-combination cream (Kligman's formula), but prolonged use is associated with adverse effects. Objectives: To compare the efficacy and safety of topical 10% isoniazid cream versus triple combination cream in the treatment of mixed melasma. Methods: This study was conducted at the Department of Dermatology, CMH Gujranwala, from 1st Sep 2024 to 31st March 2025. A total of 140 patients clinically diagnosed with mixed melasma were randomized into two groups of 70 each. Group A received 10% isoniazid cream, and Group B received the standard triple-combination cream, applied once daily at night for 8 weeks. Both groups used broad-spectrum sunscreen during the day. Efficacy was assessed using the modified Melasma Area and Severity Index (mMASI) and the physician global assessment (PGA). Adverse effects were also recorded. Results: Group A showed a greater mean reduction in mMASI score (5.7 ± 1.4) than Group B (4.4 ± 1.6), with a significant p-value (0.001). Excellent improvement (≥75%) was achieved in 40.0% of Group A, compared with 22.9% in Group B. Fewer adverse effects were reported in the isoniazid group. Conclusion: Topical 10% isoniazid cream was more effective and better tolerated than the triple combination cream for managing mixed melasma.